Night train to Munich - Wellesley, Gordon (The Criterion Coll., 2010)
Takes viewers on a World War II era journey from Prague to England to the Swiss Alps, as Nazis pursue a Czech scientist and his daughter who are being aided by a debonair British undercover agent.
Aspect ratio 1.33:1. - New, restored high-definition digital transfer
Orig.: Großbritannien 1940
Enth. New video conversation between film scholars Peter Evans and Bruce Babington about director Carol Reed, screenwriters Frank Laudner and Sidney Gilliat, and the social and political climate in which "Night train to Munich" was made ; a booklet with essay by film critic Philip Kemp